BATF3 Protects Against Metabolic Syndrome and Maintains Intestinal Epithelial Homeostasis - Hamade, Hussein; Stamps, Jasmine T.; Stamps, Dalton T.; More, Shyam K.; Thomas, Lisa S.; Blackwood, Anna Y.; Lahcene, Nawele L.; Castanon, Sofi L.; Salumbides, Brenda C.; Shimodaira, Yosuke; Goodridge, Helen S.; Targan, Stephan R.; et al. (Frontiers in Immunology, 2022)
The intestinal immune system and microbiota are emerging as important contributors to the development of metabolic syndrome, but the role of intestinal dendritic cells (DCs) in this context is incompletely understood. BATF3 is a transcription factor essential in the development of mucosal conventional DCs type 1 (cDC1). We show that Batf3-/- mice developed metabolic syndrome and have altered localization of tight junction proteins in intestinal epithelial cells leading to increased intestinal permeability. Treatment with the glycolysis inhibitor 2-deoxy-D-glucose reduced intestinal inflammation and restored barrier function in obese Batf3-/- mice. High-fat diet further enhanced the metabolic phenotype and susceptibility to dextran sulfate sodium colitis in Batf3-/- mice. Antibiotic treatment of Batf3-/- mice prevented metabolic syndrome and impaired intestinal barrier function. Batf3-/- mice have altered IgA-coating of fecal bacteria and displayed microbial dysbiosis marked by decreased obesity protective Akkermansia muciniphila, and Bifidobacterium. Thus, BATF3 protects against metabolic syndrome and preserve intestinal epithelial barrier by maintaining beneficial microbiota.